Natural products for the management of diarrhea: a systematic review of clinical efficacy, safety, and certainty of evidence - Camila Bach; Carolina Silva Schiebel; Lara Luisa Valerio de Mello Braga; Ana Carolina Vieira Ulysséa Fernandes; Mariana Avancini; Gabriel Ferreira Fernandes; Jonatan Zaleski; Jessica Boschini D’Agostin; Daniele Maria-Ferreira (Frontiers in Pharmacology, 2026)
Introduction Diarrhea is a common gastrointestinal disorder caused by infections, inflammatory diseases, or treatment‐related toxicity, particularly from chemotherapy and radiotherapy, often compromising treatment adherence and quality of life. Natural products have been increasingly investigated as complementary therapeutic strategies; however, their clinical efficacy, safety, and certainty of evidence remain unclear. Methods This systematic review evaluated clinical efficacy, safety, and certainty of evidence of natural products for the management of diarrhea in oncological and non‐oncological settings. The review followed PRISMA guidelines and was registered in PROSPERO (CRD42025572477). PubMed, MEDLINE, and the Cochrane Library were systematically searched to identify human clinical trials evaluating natural products for diarrhea. Certainty of evidence was assessed using the GRADE approach. Results and Discussion Ten studies met the inclusion criteria and evaluated interventions including Aloe vera (L.) Burm. f [Asphodelaceae; Aloe barbadensis], partially hydrolyzed guar gum, Berberis aristata DC [Berberidaceae], and multibotanical herbal formulations such as Entoban and Amoebex. Most studies reported significant improvements in diarrhea-related outcomes, including reduced stool frequency and severity, improved stool consistency, and relief of associated gastrointestinal symptoms. An exploratory narrative synthesis suggested context-specific mechanisms of action, with microbiota modulation and anti-inflammatory effects more frequently associated with treatment-related diarrhea, whereas antimicrobial activity and intestinal barrier support appeared more relevant in nononcological conditions. However, the certainty of evidence was predominantly low to very low because of methodological limitations, including small sample sizes, inadequate blinding, heterogeneous outcome measures, and reliance on single-study evidence. Safety reporting was generally insufficient, although most interventions were associated with few reported adverse events. Complementary pharmacological evidence was used to contextualize potential herb-drug interactions, highlighting important safety considerations, particularly for patients receiving anticancer therapies with narrow therapeutic indices. Overall, natural products show promise as supportive interventions for diarrhea management; however, the current evidence is insufficient to support definitive clinical recommendations. High-quality randomized controlled trials with standardized outcome measures and comprehensive safety assessments are needed to establish their therapeutic value. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/view/CRD42025572477 .